The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
CALL in a Climate of Change: Adapting to Turbulent Global Conditions – Short Papers From EUROCALL 2017 2017
DOI: 10.14705/rpnet.2017.eurocall2017.691
|View full text |Cite
|
Sign up to set email alerts
|

Can an interactive digital game help French learners improve their pronunciation?

Abstract: This study examines the effects of the pedagogical use of an interactive mobile digital game, Prêt à Négocier (PàN), on improving learners' pronunciation of French as a Second Language (FSL), using three holistic measures: comprehensibility, fluency, and overall pronunciation. Two groups of FSL learners engaged in different types of game-playing over one month: while the experimental group played PàN, the control group engaged in paper-based gamified information gap activities. Following a pre-test/post-test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…As the only clearly negative result, Cardoso et al (2017) demonstrated that using a gamified tool (Prêt à Négocier) in a French course of intermediate level, did not show significant differences on oral skills (comprehensibility and fluency) between a treatment and a control group.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…As the only clearly negative result, Cardoso et al (2017) demonstrated that using a gamified tool (Prêt à Négocier) in a French course of intermediate level, did not show significant differences on oral skills (comprehensibility and fluency) between a treatment and a control group.…”
Section: Resultsmentioning
confidence: 90%
“…Practically all of them were conducted with the help of free applications that can be easily accessed or downloaded from the Internet and used whether on a computer or a mobile device. Most experiments incorporated a gamified resource especially created for the study (Berns, et al & Dodero, 2016;Cardoso, et al 2017;Liu, et al 2016;Palomo-Duarte et al, 2016;Perry, 2015), whereas Duolingo and Kahoot were the most popular commercial apps (Bustillo, et al 2017;Gafni, et al 2017;Hung, 2017;Iaremenko, 2017;Mateo-Gallego & Ruiz Yepes, 2018;Munday, 2016). English stands out among the second languages studied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations